Usefulness of argon plasma coagulation for superficial esophageal squamous cell neoplasia in patients at high risk or with limited endoscopic resectability - Kubota, Yo; Tanabe, Satoshi; Ishido, Kenji; Yano, Takafumi; Wada, Takuya; Watanabe, Akinori; Azuma, Mizutomo; Katada, Chikatoshi; Koizumi, Wasaburo (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Endoscopic resection is the standard treatment for superficial esophageal squamous-cell neoplasia (SESCN). However, we encounter patients in whom endoscopic resection is difficult to perform. We retrospectively studied the usefulness of argon plasma coagulation (APC) in patients with SESCN.Materials and Methods: The study comprised 45 patients with SESCN (81 lesions) who underwent APC in our hospital from March 1999 through August 2016. Clinicopathological characteristics, treatment time, the presence or absence of metastasis and recurrence, adverse events, and outcomes were studied.Results: The median follow-up was 40 months. The median age was 70 years. The tumor diameter was 10 mm or longer in 48 lesions and less than 10 mm in 33 lesions. The median treatment time was 22 minutes. The reasons for selecting APC were as follows: technical difficulty caused by the presence of metachronous multiple lesions in the radiation field after chemoradiotherapy or close proximity to the ulcer scar remaining after endoscopic treatment in 49 lesions (60.4%), and the presence of underlying diseases in 26 lesions (32.0%). Adverse events occurred in 2 patients (4.4%) who had hypoxemia due to over-sedation. Two lesions (2.5%) recurred locally but could be locally controlled by additional APC. No patient had metastasis or recurrence or died of esophageal neoplasia. The 3-year overall survival rate was 87.0%, and the 3-year recurrence-free survival rate was 97.2%.Conclusion: APC can be a useful treatment option for SESCN in patients with a limited life expectancy, poor performance status, or technical difficulty in resection of superficial neoplasms.